Development of Integrated ESD PBL E-LKPD to Improve Critical Thinking Skills and Environmental Literacy of Phase E Students at SMA N 1 Seyegan - Saraswati; Suhartini (Postgraduate, University of Mataram, 2024)
This study aims to determine the feasibility, practicality, and effectiveness of E-LKPD Problem Based Learning (PBL) integrated with Education for Sustainable Development (ESD) in ecosystem material to improve critical thinking skills and environmental literacy of SMA phase E students. This study is a Research and Development (R&D) study with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). E-LKPD was evaluated by experts, practitioners, and tested for its effectiveness on SMA N 1 Seyegan phase E students. Data collection instruments used interviews, questionnaires, and test instruments. Instrument validity techniques involve content validation by experts and empirical validation using statistical programs based on the magnitude of the Rcount ≥ Rtable value or Sig value < 0.05. Data analysis techniques use the manova test at a significance level of 0.05 and n-gain score. The results of this development research indicate that the development of E-LKPD is assessed from the feasibility of material experts and media experts to obtain a very good category; assessed from biology teacher practitioners and students to obtain a very practical category; and effectively improve critical thinking skills and environmental literacy of students. This result is supported by the average gain score results which show that there is an increase in critical thinking skills and environmental literacy of students in the fairly effective category of 0.60 and 0.72 whose learning uses E-LKPD PBL integrated with ESD.